Renewal of Islamic Education Management at Senior High Schools - M Muhsin Ks; Imam Suprayogo; Ahmad Barizi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the modernization of Islamic education management by Kiai at Senior High School Trensains Tebuireng, utilizing a qualitative case study approach. Methods of data collection include observation, interviews, and documentation, while data analysis employs reduction, presentation, and conclusion verification techniques. The findings reveal that updates to the Islamic boarding school's management by Kiai are systematic, incremental, open, and ongoing across various components. These updates include the unification of curricula, the adoption of a recruitment system based on competence and ethics, enhancements to student selection processes, the introduction of collaborative learning, the assurance of minimum government infrastructure standards, the expansion of fundraising avenues, and the establishment of bidirectional communication with the community. These reforms have positively influenced the school's reputation and the competence of its students.